Answer:64
Step-by-step explanation:
-x-3y=-26
6x+3y=21
---------------
3y cancels out.
-x=-26
6x=21
--------------
5x=-5
x=-1
Biden 2020
Stupid nevada taking so long to vote and see you all on purge night
x f(x)
−2 0.22
−1 0.67
0 2
1 6
2 18
g(x) = 3x + 3
x g(x)
−2 3.11
−1 3.33
0 4
1 6
2 12
Based on the tables, what is the solution to the equation 2(3)x = 3x + 3?
A)x=-1
B)x=0
C)x=1
D)X=6
Answer:
X will equal 1
Answer: The X axis.
Step-by-step explanation: You can tell because if you fold the paper in half hamburger style then the two shapes line up and they fold across the X axis.